Digital History and Hermeneutics Between Theory and Practice - Tatarinov, Juliane; Fickers, Andreas (Studies in Digital History and Hermeneutics, 2022)
For doing history in the digital age, we need to investigate the "digital kitchen" as the place where the "raw" is transformed into the "cooked". The novel field of digital hermeneutics provides a critical and reflexive frame for digital humanities research by acquiring digital literacy and skills. The Doctoral Training Unit "Digital History and Hermeneutics" is applying this new digital practice by reflecting on digital tools and methods.